Impact of environmental protection policy on non-point source pollution of planting industry - Fu, Zhaogang; Hu, Shanshan; Deng, Yitong; Qi, Meihui (Bangladesh Journal of Botany, 2023)
The control of agricultural non-point source pollution, especially the problem of planting non-point source pollution, is of great significance to comprehensively promote rural revitalization. First, based on the panel data from 2006 to 2020 and using the DID model 30 provinces were classified in China. It is found that environmental protection policies have a significant inhibitory effect on the non-point source pollution of the planting industry, and the effect is more obvious over time. From the perspective of heterogeneity analysis, the eastern region, the economic crop planting region, and the rural areas close to the provincial capital have more significant pollution control. Secondly, the environmental protection policy plays a role in reducing the non-point source pollution emissions of the planting industry through the intermediary effects such as the guiding mechanism, the economic incentive mechanism, and the supervision mechanism. Finally, the corresponding policy implications are proposed. Bangladesh J. Bot. 52(2): 559-567, 2023 (June) Special